Sistem Monitoring Daya dan Arus Listrik Pada Pembakit Listrik Tenaga Bayu Berbasis Thingspeak - Anisah, Siti; Tharo , Zuraidah; Prayogi, Faisal (Universitas Medan Area, 2024)
PLTB is a renewable energy solution that can reduce dependence on fossil fuels and reduce greenhouse gas emissions. To ensure operational efficiency and reliability, a monitoring system is needed. The monitoring system used in this paper consists of sensors integrated with Arduino to collect real-time data on wind speed, output voltage, current and operational conditions of Tingspeak-based turbines. The data collected by the sensors is sent to the Arduino Uno, which then processes the data for further analysis. Implementation of this Arduino Uno-based monitoring system also allows early detection of potential problems, so that preventive action can be taken to increase efficiency. The results of this research show that the factors that influence the performance of wind turbines are the voltage and current. So for this reason, a tool was created that can monitor and display the amount of voltage and current produced by the Wind Turbine. This tool uses the PZEM-004T sensor to measure current and voltage. The sensor measurement results are processed by the Arduino Nano R3 and then displayed on the LCD and ESP-01 chip to WiFi, then the data will be sent to the Thingspeack cloud server to display the current and voltage